1989
DOI: 10.1017/s1446788700030780
|View full text |Cite
|
Sign up to set email alerts
|

On the Projective Cover of an orbit space

Abstract: In this paper, we obtain the projective cover of the orbit space X/G in terms of the orbit space of the projective space of X, when X is a Tychonoff G-space and G is a finite discrete group. An example shows that flniteness of G is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…(b) Let / : X -» Y be a dp-epimorphism. Then for a regular closed set H of Y we have C l / ( C l / - 1 Finally, the uniqueness of Ef follows by recalling that a dp-map is a c-map [5, 6G3]. U…”
Section: Proof: the Results Is Immediate Ifmentioning
confidence: 99%
See 3 more Smart Citations
“…(b) Let / : X -» Y be a dp-epimorphism. Then for a regular closed set H of Y we have C l / ( C l / - 1 Finally, the uniqueness of Ef follows by recalling that a dp-map is a c-map [5, 6G3]. U…”
Section: Proof: the Results Is Immediate Ifmentioning
confidence: 99%
“…By inducing an action of a discrete group G on EX, where X is a G-space, Azad and Agrawal [1] showed that if G is finite, then E(X/G) is homeomorphic to the orbit space EX/G. An example to show that the above result may fail if G is infinite, is provided in [1].…”
Section: Tk Das [2]mentioning
confidence: 99%
See 2 more Smart Citations